APLIKASI VOIP BERBASIS WEB UNTUK KOMUNIKASI ANTAR KARYAWAN PADA UNIVERSITAS BUDI LUHUR - Painem Painem (Universitas Budi Luhur, 2013)
The business world is growing very rapidly. To improve the efficiency of business processes in a company, it is necessary to smooth and timely communication. Thus, communication becomes something vital at this time. One issue that often arises is the lack of communication media that provided by the company. Thus, employees are difficult to establish communication between them to support the company needs. To have a communication medium is one of the goao of the company, in order to facilitate communication between the employees, where they can communicate each other either through medium of sound in which they can communicate without they have to move from the table their work and also can log their events, using this application, which their sound can be recorded and strored in server. Companies find it easier to monitor employees. Obviously this will be an advantage because the communications between employees will become more smoothly. Thus, employees at the company's communication issues expected to be resolved soon with the application.Keywords: VoIP, Client, Server, RTP